2022
DOI: 10.3389/fmicb.2022.919044
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Baijiu: The Perfect Works of Microorganisms

Abstract: Chinese Baijiu is one of the famous distilled liquor series with unique flavors in the world. Under the open environment, Chinese Baijiu was produced by two solid-state fermentation processes: jiuqu making and baijiu making. Chinese Baijiu can be divided into different types according to the production area, production process, starter type, and product flavor. Chinese Baijiu contains rich flavor components, such as esters and organic acids. The formation of these flavor substances is inseparable from the meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 135 publications
0
49
0
Order By: Relevance
“…With the development of sequencing technology, researchers can obtain the genetic sequences of various species and types of genomes, including the nuclear genome, chloroplast genome, and mitochondrial genome ( Chakraborty et al, 2020 ; Bao et al, 2022 ; Tu et al, 2022 ; Bao et al, 2023 ). In the process of analyzing the genetic information of species, researchers have found that the probability of synonymous codons of different species being used is not always equal.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of sequencing technology, researchers can obtain the genetic sequences of various species and types of genomes, including the nuclear genome, chloroplast genome, and mitochondrial genome ( Chakraborty et al, 2020 ; Bao et al, 2022 ; Tu et al, 2022 ; Bao et al, 2023 ). In the process of analyzing the genetic information of species, researchers have found that the probability of synonymous codons of different species being used is not always equal.…”
Section: Discussionmentioning
confidence: 99%
“…These original yeasts were further categorized into 12 species by blasting against the NCBI database, including S. cerevisiae , W. anomalus , Saccharomycopsis fibuligera , P. kudriavzevii , Pichia manshurica , Hyphopichia burtonii , Clavispora lusitaniae , Candida apicola , and Meyerozyma guilliermondii . Pichia , W. anomalus , and S. cerevisiae were identified as the predominant species of yeasts in light-flavor Baijiu , which could synthesize alcohols and esters that contributed to the flavor of light-flavor Baijiu ( Tu et al, 2022 ). Pichia , W. anomalus , and S. cerevisiae and accounted for 28.57, 20, and 14.29% of the yeast population, respectively, in this study.…”
Section: Resultsmentioning
confidence: 99%
“…will further coordinate and balance, thus enhancing the quality of Baijiu and lowering its pungency. Generally, the aging process of Baijiu is predominantly dark, and the storage time is up to 2–5 years [ 27 , 28 , 29 , 30 ]. In order to shorten the aging time of Baijiu, the distillery has innovated a new aging technique based on practical experience.…”
Section: Introductionmentioning
confidence: 99%